The Development of Bruce Wayne's Duality of Identity in The Dark Knight Trilogy: A Jungian Psychoanalysis Approach: Perkembangan Dualitas Identitas Bruce Wayne dalam The Dark Knight Trilogy: Pendekatan Psikoanalisis Jungian - Raditya Nugraha (Universitas Negeri Surabaya, 2025)
This thesis utilized Carl Jung's psychoanalytic theories to examine the psychological intricacy of Bruce Wayne's dual identity as it was portrayed in Christopher Nolan's Batman Trilogy. It focused on the ideas of Persona, Shadow, and Individuation. The study aims to explore how Bruce Wayne's trauma-driven and justice-seeking transformation into Batman with the guidance of Jungian psychoanalysis and textual analysis of significant scenes and dialogues from the trilogy, the study reveals the psychological growth and symbolic meanings of these characters. The key finding presented in the study's result. Is that, according to Jung's theories of persona, shadow, and individuation, Bruce Wayne's internal struggle between his public persona and his shadow as Batman represents a profound psychological tension.